Evidence of cryptic lineages within a small South American crocodilian: the Schneider’s dwarf caiman Paleosuchus trigonatus (Alligatoridae: Caimaninae) - Pedro Senna Bittencourt; Zilca Campos; Fábio de Lima Muniz; Boris Marioni; Bruno Campos Souza; Ronis Da Silveira; Benoit de Thoisy; Tomas Hrbek; Izeni Pires Farias (PeerJ, 2019)
Schneider’s dwarf caiman Paleosuchus trigonatus is one of the smallest living crocodilians. Due to its broad distribution, cryptic behavior, and small home range, the species is well suited for the study of phylogeographic patterns on a continental scale. Additionally, this species is under threat due to habitat loss, trade and harvest, but is considered at low conservation risk by the IUCN. In the present study we test the hypothesis that P. trigonatus is comprised of geographically structured lineages. Phylogenetic reconstructions of the mitochondrial cytochrome b gene and single locus species discovery methods revealed the existence of two well-supported lineages within P. trigonatus—an Amazonian and Guianan lineage. Fossil calibrated divergence of these lineages was estimated to have occurred in the Late Miocene (7.5 Ma). The hypothesis that the Atlantic coast drainages might have been colonized from the southeast or central Amazon is supported by demographic metrics and relatively low genetic diversity of the Coastal and upper Branco populations when compared to the Amazon basin populations. The Amazon basin lineage is structured along an east-west gradient, with a sharp transition in haplotype frequencies to the east and west of the Negro and Madeira rivers. These lineages are already under anthropogenic threat and, therefore, are conservation dependent. Recognition of these lineages will foster discussion of conservation future of P. trigonatus and these lineages.